Effect of unsteady aerodynamic loads on driving safety and comfort of trains running on bridges. Issue 13 (October 2020) - Han, Yan; Liu, Ye; Hu, Peng; Cai, CS; Xu, Guoji; Huang, Jiaying
In order to investigate the effects of unsteady aerodynamic loads on the driving safety and comfort of trains running on bridges, a three-dimensional and multi-body system model of train–track–bridge was established and the dynamic responses of the coupling system were calculated by combining the finite element software ANSYS with the multi-body dynamics software SIMPACK. The driving safety and comfort of a train running on a bridge under steady and unsteady aerodynamic loads were compared and analyzed. The effects of different crosswind speeds on the driving safety of the train running on the bridge under unsteady aerodynamic loads were studied. It is found that the index values of the driving safety and comfort of the train at the speed of 200–300 km/h without the wind loads are smaller (meaning safer) than those of the train under the wind loads. When the average speed of crosswind is 20 m/s, the driving safety assessment results of the train are better and its comfort assessment results are more conservative with considering the unsteady aerodynamic loads than the steady wind load case. When the average speed of crosswind is smaller than 10 m/s and the train speed is 250 km/h, the driving safety and comfort of the train on the bridge meet the requirements, and the level of stability can reach "good" or above. Through the analysis of driving safety of the train on the bridge under different crosswind speeds, the threshold values of safe driving were obtained, which can provide a better basis for the safe operation of trains on bridges.